Current perspectives on learning disabilities - Burkhardt, Sandra A.; Obiakor, Festus E.; Rotatori, Anthony F. (Amsterdam : JAI, 2004)
This book addresses prominent trends in learning disabilities in a systematic and comprehensive manner. The book's major premise focuses on the early identification and intervention of learning disabilities which can positively impact a child's academic performance by making achievement possible. Critical information is discussed to prevent undetected learning disability which may lead even an older student to struggle with poor grades, low self-esteem, loss of interest in higher education, and reduced employment. The book presents current knowledge based information on forces outside of the school that impact the field of learning disabilities such as, advances in evaluation and testing, diagnostic imaging of the functioning brain, evolving ways of conceptualizing learning disabilities that include multicultural perspectives, challenges to conventional views of intelligence and new federal laws that place performance demands upon schools. Additionally, instructional best practice approaches and new technology is provided that should enhance the academic teaching of students. There is even a chapter on a model inner city program that discusses teaching of students with severe learning difficulties. Finally, there is a chapter on the role that school counsellors play in planning for college and careers in a climate of societal expectation that promotes a college education as an obtainable goal for students with learning disabilities. The book is valuable to general and special education teaches, school psychologists, teacher educators, practicing mental health clinicians, and school and career counsellors. A secondary audience is graduate students in special education and counselling graduate programs who need a comprehensive resource book on current trends and best practices.
Conceptualizations of learning disabilities : beyond the ability-achievement discrepancy / Julia A. Deisinger -- Non-verbal learning disabilities / Sandra Burkhardt -- Multicultural learners with learning disabilities : beyond Eurocentric perspectives / Festus E. Obiakor and Cheryl A. Utley -- Neurological and neuropyschological aspects of learning and attention problems / Roger Stefani -- Curriculum modifications for students with learning disabilities / Ann Richards and Elizabeth Dooley -- Technology resources for persons with learning disabilities / Jeffrey P. Bakken and Brian W. Wojcik -- Comprehensive assessment of students with learning disabilities / Anthony F. Rotatori and Tim Wahlberg -- Career development for persons with learning disabilities / Pamela Castellanos and Dale Septeowski -- Impact of the Americans With Disabilities Act on persons with learning disabilities / Patrick A. Grant, Richael Barger-Anderson and Patrice A. Fulcher -- The impact of the No Child Left Behind Act / Candace Baker and Beverly Gulley -- Trends in teacher preparation for teaching students with learning disabilities / Meg Carroll -- Support services for college students with learning disabilities / Sunday O. Obi -- Wings Academy : a new charter school for students who learn differently / Dani La Porte and Nicola Leather.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Learning disabled -- Education; Learning disabilities; Teaching of specific groups & persons with special educational needs; Education -- Special Education -- Mental Disabilities; Electronic books